2013
DOI: 10.3109/03630269.2013.769886
|View full text |Cite
|
Sign up to set email alerts
|

Sistani Population: a Different Spectrum oF β-Thalassemia Mutations From other Ethnic Groups of Iran

Abstract: This study aimed to characterize the molecular spectrum of β-thalassemia (β-thal) mutations and evaluate the services available for prenatal diagnosis (PND) among the Sistani population of Iran. Mutations were analyzed with amplification refractory mutation system (ARMS), gap-polymerase chain reaction (gap-PCR), multiplex ligation-dependent probe amplification (MLPA) analysis and direct sequencing. Fetal diagnosis was also confirmed by linkage analysis. Over a 9-year period (2002-2011), 405 at-risk Sistani cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, we recorded LRC as the second major component before FFP that probably was due to the type of patients and hospitals evaluated. This province is one of the most prevalent areas of thalassemia in Iran with the routine use of LRC and WRC products (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…However, we recorded LRC as the second major component before FFP that probably was due to the type of patients and hospitals evaluated. This province is one of the most prevalent areas of thalassemia in Iran with the routine use of LRC and WRC products (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all studies were conducted in Turkish Azeri, Northwestern Iran, West Iran, and Southwest Iran and Iranian Kurds reported the latter mutation as the most common beta-globin gene defect (23)(24)(25) . Moreover, it has been previously reported as having the highest rate in other populations in the surrounding countries, such as Jordan, Syria, Kuwait, and Saudi Arabia (19) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was detected at low frequency in Mediterranean Arab countries including Syria (1.4%), Lebanon (1%), Israeli Arab (6%), Egypt (5.6%), Tunisia (4.4%), and Algeria (0.9%) (19) . The Cd8/9+G mutation is of Asian-Indian origin, and one Iranian study showed that this mutation is less common among the Sistani Iranian population (25) . Kerman city in Iran recorded it at 4.9% (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the genetic diversity of multiple disorders, genomes molecular evaluation is required for the entire world (8)(9)(10). While diagnostic methods are developed, yet the wide majority of ID causes do not have definitive molecular detection.…”
Section: Definitionsmentioning
confidence: 99%